2018
DOI: 10.1097/mao.0000000000001969
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Mineral Density of the Lateral Skull Base and its Relation to Obesity and Spontaneous Cerebrospinal Fluid Leaks

Abstract: There appears to be no difference between the BMD of the lateral skull base as it relates to obesity or spontaneous CSF leaks compared with normal weight controls. These findings suggest the BMD does not have a significant role in the development of lateral skull base thinning or dehiscence leading to CSF leaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…A history of temporal bone trauma should raise suspicion for post-traumatic CSF leak, as demonstrated by Case 1. Conversely, a history of obesity, OSA and/or IIH should prompt further workup for sCSF-L (2–4,9–14,16–28,37). However, as demonstrated by cases 2 and 3, these demographic features need not be present for a patient to develop a “spontaneous” leak.…”
Section: Discussionmentioning
confidence: 97%
“…A history of temporal bone trauma should raise suspicion for post-traumatic CSF leak, as demonstrated by Case 1. Conversely, a history of obesity, OSA and/or IIH should prompt further workup for sCSF-L (2–4,9–14,16–28,37). However, as demonstrated by cases 2 and 3, these demographic features need not be present for a patient to develop a “spontaneous” leak.…”
Section: Discussionmentioning
confidence: 97%
“…Of the few previous tegmen measurement algorithms that have been reported, only one has focused on tegmen bone mineral density. 13 Our measurement algorithm is different from that one in that we designed ours to focus specifically on areas of potential pathophysiology. In contrast, previous algorithms have taken a broader measurement of the tegmen as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any significant differences in bone mineral density between obese and non-obese patients, in agreement with one previous quantitative study by Hatch et al from 2018, which reported no difference in bone mineral density of the lateral skull base as it relates to obesity or spontaneous CSF otorrhoea compared with normal-weight controls. 13 To date, the Hatch et al study remains the only published study on the quantitative analysis of tegmen bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 More recently, increased attention has been paid to the effects of obesity on lateral skull base. 3,12-19…”
Section: Discussionmentioning
confidence: 99%